63 Learning disability awareness week at great ormond street hospital. (23rd February 2023) - West, Ema-Mae; Oulton, Kate; Walker, Alexander; Whyte, Lauren
Abstract : Background: Learning Disability Week is an annual campaign from Mencap, dedicated to educating and raising awareness of learning disabilities. This year the theme of Learning Disability Week (20-26 th June) was 'Living Life with a Learning Disability'. The campaign focuses on 'education and raising awareness about Learning Disabilities, ending discrimination and stigmas surrounding Learning Disabilities, and fighting and campaigning for equality and fair society' (Mencap). Aim: The purpose of this presentation is to share examples and experiences of inclusive activities undertaken during LD Awareness week in a specialist children's hospital. Methods: During the week the Learning Disability Team supported numerous guest visitors, activities and celebrations, and education sessions throughout the trust to promote awareness and engage positively with families and staff. Examples included music therapy, education, training on the use of specialist beds, and Dogs for Autism. The Learning Disability team collaborated with the Van Gogh Alive Exhibition on a spectacular display of sunflowers that brightened up the entrance of the hospital. We raised awareness by utilising Van Gogh's notable sunflower theme, as globally the sunflower is recognised as the symbol for hidden disabilities. During LD week the sunflower decals on the floor led the way to a stand in the main reception where the activities and information sharing took place. The Learning Disability team were supported during the week by Safeguarding, Play team, Neurodisability, Music Therapy, hospital school, Arts Team, communications team. Discussion: Throughout the week the activities and education sessions were well attended and provided the team with a wonderful opportunity to engage with patients, families, and staff. The planning of the week took a considerate amount of time, including focus on health and safety, infection control and current COVID guidelines/social distancing measures. The support from members of multidisciplinary teams allowed for the planning and success of the week.